Reviving the Cultural Dimension of Rural Regional Planning: Lessons from Howard W. Odum and the Cultural Regionalists. (20th October 2022) - Hibbard, Michael; Frank, Kathryn
Abstract: The recent cultural turn in planning has had important influences across the globe. However, insufficient attention has been given to one of the most interesting aspects of the planning-culture nexus, the potential of planning in integrating the social life of regions. That approach, termed cultural regionalism, shaped thinking about regional planning in the U.S. in the 1920s and '30 s, but had essentially disappeared by the 1950s. We explore cultural regionalism through a review of the work of Howard W. Odum and his colleagues and then consider how contemporary planning might benefit from exposure to it.